Methicillin-susceptible and -resistant Staphylococcus aureus with high-level antiseptic and low-level mupirocin resistance in Malaysia - Moghaddam, Hamed Ghasemzadeh; Belkum, Alex van; Awang Hamat, Rukman; Wamel, Willem van; Neela, Vasanthakumari (Mary Ann Liebert, 2014)
The prevalence and spread of mupirocin and antiseptic resistance among colonizing and infectious Staphylococcus aureus were determined. S. aureus isolated from anterior nares and infection sites of patients hospitalized in the largest tertiary care referral hospital in Malaysia was investigated for mupirocin and antiseptic susceptibility testing, and for PCR detection of mupA, qacA/B, and smr genes. Twelve isolates showed resistance to mupirocin by disk diffusion, of which 10 (3.8%) harbored the mupA gene. Minimum inhibitory concentrations (MICs) ranged from 64 to 768 μg/ml for mupA positive and below 46 μg/ml for negative isolates. The mupA was more common among ST239 isolates (70%). The qacA/B was carried in 67 out of 95 methicillin-resistant Staphylococcus aureus (MRSA) (70.5%) and 3 out of 164 methicillin-susceptible Staphylococcus aureus (MSSA) (1.8%), while smr was carried in 6 out of 95 MRSA (6.3%) strains. MICs ranged from 3.9 to 15.6 μg/ml for benzethonium chloride (BTC) and benzalkonium chloride (BKC), and from 10.3 to 20.7 μg/ml for chlorhexidine digluconate (CHG). Isolates with qacA/B and smr or qacA/B alone showed higher MIC (20.7 μg/ml for CHG and 15.6 μg/ml for BTC and BKC) than the isolates that lacked antiseptic resistance genes (10.3 μg/ml for CHG and 3.9 μg/ml for BTC and BKC). In 16 cases, ST239 was isolated from the infection site and the nares simultaneously, and shared identical resistance patterns (qacAB or qacAB+smr), suggesting possible endogenous infection. Spread of low-level mupirocin resistance expressing ST239 MRSA and high-level resistance expressing emerging ST1, co-existing with antiseptic-resistant genes showing elevated MICs, should be monitored for effective infection control.